Corrected QT interval prolongation during anesthetic induction for laryngeal mask airway insertion with or without cisatracurium. Issue 5 (May 2018) - Xuan, Chengluan; Wu, Nan; Li, Yanhui; Sun, Xiaoting; Zhang, Qunshu; Ma, Haichun
Objective: This study was performed to observe the occurrence of corrected QT (QTc) interval prolongation during anesthetic induction for laryngeal mask airway insertion and the effects of cisatracurium administration on the QTc interval. Methods: Eighty-eight patients were assigned to two groups: the cisatracurium administration group (n = 45) and non-cisatracurium administration group (n = 43). The QTc interval was continuously recorded by a 12-lead Holter electrocardiogram beginning in the hospital ward and continuing until after anesthetic induction. Results: In the cisatracurium administration group, the QTc interval significantly increased from 417.9 ± 27.9 to 451.6 ± 32.5 ms after arrival in the operating room and significantly decreased to 432.4 ± 32.5 ms after a 15-minute rest; it significantly increased to 459.7 ± 23.8 ms again after propofol and fentanyl injection. However, the QTc interval decreased after cisatracurium injection. In the non-cisatracurium administration group, the QTc interval initially showed changes similar to those in the cisatracurium group until fentanyl and propofol were injected. Conclusions: The QTc interval was significantly prolonged on arrival in the operating room and after propofol and fentanyl injection. The QTc interval did not significantly change by laryngeal mask airway insertion regardless of the administration of cisatracurium.